15.3k views
1 vote
Please solve this for me T_T

If

x - √(a)
is a factor of

2 {x}^(4) - 2 {a}^(2) {x}^(2) - 3 {x} + 2 {a}^(3) - 2 {a}^(2) + 3
then find the value of

a


1 Answer

0 votes

Answer:


\boxed{\sf \ a = 1 \ }

Explanation:

let s assume that a >=0 so that we can take the square root

if
x-√(a) is a factor of this expression it means that
√(a) is a root of it

it comes


2*(√(a))^4-2*a^2*(√(a))^2-3*√(a)+2*(√(a))^3-2(√(a))^2+3=0

So


2*a^2-2*a^3-3*√(a)+2*a*√(a)-2*a+3=0

we can notice that 1 is a trivial solution as

2-2-3+2-2+3=0

so the answer is 1

let s double check

if a =1

the expression is


2x^4-2x^2-3x+2-2+3=2x^4-2x^2-3x+3

and we can write


2x^4-2x^2-3x+3=(x-1)(2x^3+2x^2-3)

so 1 is the correct answer

User Shubham Sahu
by
4.3k points